2014
DOI: 10.1016/j.jhep.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of HO-1 and carbon monoxide in ethanol-induced hepatocyte cell death and liver injury in mice

Abstract: Background and Aims Alcoholic liver disease is associated with inflammation and cell death. Heme oxygenase-1 (HO-1) is a stress-inducible enzyme with anti-apoptotic and anti-inflammatory properties. Here we tested the hypothesis that induction of HO-1 or treatment with a carbon monoxide releasing molecule (CORM) during chronic ethanol exposure protects and/or reverses ethanol-induced liver injury. Methods Female C57BL/6J mice were allowed free access to a complete liquid diet containing ethanol or pair-fed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…The haemeoxygenase-1 (HO) system is the primary pathway present in many tissues to catalyze the oxidation of heme, a potentially harmful pro-oxidant, to the biologically active molecules biliverdin, iron and carbon monoxide (CO) [1,2]. To date, two main distinct isoforms of HO have been identified: HO-1 and HO-2.…”
Section: Introductionmentioning
confidence: 99%
“…The haemeoxygenase-1 (HO) system is the primary pathway present in many tissues to catalyze the oxidation of heme, a potentially harmful pro-oxidant, to the biologically active molecules biliverdin, iron and carbon monoxide (CO) [1,2]. To date, two main distinct isoforms of HO have been identified: HO-1 and HO-2.…”
Section: Introductionmentioning
confidence: 99%
“…Indication for a potential use of CORM-A1 as pharmaceutical originates from its multiple bioactivities, such as anti-inflammatory, anti-apoptotic and antioxidant effects provided by the small amounts of CO released [11,12]. To date, CORM-A1 has been shown to be highly protective in several rodent inflammatory-related disorders, such as experimental autoimmune encephalomyelitis [13], high-fat diet induced obesity [14], and chronic ethanol-induced liver injury [15]. Our own findings demonstrated that the pharmacological application of CO by CORM-A1 protected mice from developing T1D [16].…”
Section: Introductionmentioning
confidence: 99%
“…Mice were treated with CoPP along with carbon monoxide releasing molecule-A1 (CORM-A1), a CORM to induce HO-1 expression during ethanol feeding or once injury had been established. This experimental result proved that induction of HO-1 or treatment with a CORM during chronic ethanol exposure protects and/or reverses ethanol-induced liver injury [39]. Study showed that chronic ethanol feeding increased LPS-stimulated TNF-α expression by Kupffer cells, linked with a shift to an M1 macrophage polarization.…”
Section: The Role Of Lipopolysaccharide and Toll Like Receptors In Almentioning
confidence: 52%
“…Research showed that when mice were treated with cobalt protoporphyrin (CoPP) to induce HO-1 expression, ethanolinduced sensitivity to LPS was ameliorated [39]. Mice were treated with CoPP along with carbon monoxide releasing molecule-A1 (CORM-A1), a CORM to induce HO-1 expression during ethanol feeding or once injury had been established.…”
Section: The Role Of Lipopolysaccharide and Toll Like Receptors In Almentioning
confidence: 99%